The Development of Convicted Children’ English through the English Communication Coaching Clinic - Mohamad dziqie aulia al farauqi; Khusnul Khatimah (Pusat Penerbitan Ilmiah Universitas Muhammadiyah Kalimantan Timur, 2019)
As the output of community services research (Iptek Untuk Masyarakat (IuM) UMKT) held by the writers, this article casted lights on the development and coaching clinic of English language for convicted children of Lapas Klas II A in Samarinda city. The object of research was 37 people aged minimum 16. This article assumed that the organized and discipline condition of prison is an opportunity to improve juvenile convicts’ English capacity. Whereby, the learning condition is one paramount factor of strengthening people’s capability of English. The result of this program are (1) The knowledge and understanding English of the children were improved. (2) The fun presented in this program and the interactive method of plays attracted the children’s attention to learn. (3) The interest of children in learning English was improved (accounted for 92% of the student’s interest is improved within a 2 month period) (4) the convict’s capability of English was amounted of approximately 40% of students could speak simple English.